Pengaruh Strategi Pembelajaran Online Terhadap Keaktifan Belajar Siswa Kelas IVB Di SDN Cengkareng Timur 05 Pagi - Indah Mentari (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2021)
This study aims to determine the effect of online learning strategies on student learning activities. The population in this study was conducted in class IVB at SDN Cengkareng Timur 05 Pagi found 32 students and the research sample was class IVA at SDN Cengkareng Timur 05 Pagi which was collected by 30 students with data collection techniques using questionnaires. This research uses quantitative research with survey method. The results of this study obtained an rxy of 0.902 with a partial test (t test) of tcount = 7.877 > 2.042 with a significance of 0.000 <0.005, this result was rejected and accepted with a correlation coefficient of 82.1% which means that there is a correlation between online learning strategie on student learning activity and the coefficient of determination of the independent variable, namely online learning strategy on the dependent variable of student learning activity of 67.4%. This shows that 67.4% of online learning strategies affect student learning activities, while the remaining 32.6% are influenced by other factors outside of this study.